O treinamento multicomponente evita déficit de memória relacionado à neurotoxidade induzida por proteína amiloide - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Alzheimer's disease (AD) is currently the most common form of dementia. The major challenges facing AD include the lack of reliable biomarkers for early diagnosis, as well as the lack of effective preventive strategies and treatments. So, researches investigating strategies to prevent this disease have been look for the use of accessible tools with the potential to intervene in the various pathological markers of AD, including the amyloid- neurotoxicity. In the present study, using a Wistar rats, we show that a long-term multicomponent training (MT), including aerobic and anaerobic physical exercise, and cognitive exercise, is capable to prevent recognition memory deficits related to amyloid- neurotoxicity. Additionally, MT is able to avoid hippocampal lipid peroxidation, restore hippocampal antioxidant capacity and increase glutathione levels in hippocampus.
Multicomponent training avoids memory deficit related to neurotoxicity induced by amyloid protein
Keywords: Enfermagem; Doença de Alzheimer; Exerecício físico; Exercício cognitivo; Alzheimer’s disease; Treino multicomponente; Physical exercise; Cognitive exercise; Multicomponent training; CNPQ::CIENCIAS DA SAUDE